A comparison of energy storage from renewable sources through batteries and fuel cells: A case study in Turin, Italy. (14th December 2016) - Belmonte, N.; Girgenti, V.; Florian, P.; Peano, C.; Luetto, C.; Rizzi, P.; Baricco, M.
Abstract: In this paper, two alternative integrated power systems were considered: one based on photovoltaic and hydrogen technology (electrolyzer coupled with a fuel cell), the other based on photovoltaic and batteries. The two systems, designed for off-grid applications, were sized for a photovoltaic energy production in the area of Turin, Italy, to provide 3 kW maximum power, with an average daily consumption of 10.25 kWh. The systems were compared from a technical and economical point of view and a Life Cycle Assessment analysis (LCA) was performed, to identify the main contributors to the environmental impact of the systems. From a commercial point of view, fuel cell and the electrolyzer are niche products, so the hydrogen-based power system results to be more expensive with respect to Li-ion batteries. From the environmental point of view, however, LCA results show the lower burdens of the hydrogen technology. Highlights: Design and sizing of two power systems for off-grid applications in Turin area. Comparison of energy storage systems: electrolyzer coupled with fuel cell and battery. Cost analysis show that power system based on hydrogen technology is more expensive. LCA shows that electrolyzer + fuel cell has lower impact with respect to solar panels.